Biological activities of penicilliopsis sp. / Nadia Iryani binti Najri - Nadia Iryani, Najri (2011)
This study was carried out to evaluate the biological activities of Penicilliopsis sp. (KUM60280). The methanol and dichloromethane crude extracts were evaluated for their antimicrobial, antioxidant, cytotoxic and anti-human papillomavirus (HPV) activities. The amounts of total phenolic compound in the extracts were also evaluated. The antibacterial capacity was screened against Gram positive bacteria (Bacillus subtilis, B. cereus, Staphylococcus aureus, Streptococcus mutans, S. mitis, S. sanguis) as well as Gram negative bacteria (Escherichia coli, Pseudomonas auruginosa and P. vulgaris). Antifungal potentials on the other hand, were evaluated against Candida albicans, C. parasilopsis and Saccharomyces pombe by the disc diffusion method. The results of antimicrobial assay indicated that extracts of Penicilliopsis sp. were non-toxic against all the tested microorganisms. Antioxidant activity was assessed using the 2,2 diphenyl-1-picrylhydrazyl radicals (DPPH.) assay and the reducing power assay. The subfraction methanol and dichloromethane extracts of Penicilliopsis sp. was able to reduce the stable free radical DPPH. with an EC50 values of 26.8 mg/ml ± 0.05 μg/ml and 50.5mg/ml ± 0.05 μg/ml, respectively. Penicilliopsis sp. crude extracts are powerful radical scavengers based on the inhibition of scavenging component. The reducing powers of methanolic extract and dichloromethane extracts from mycelia were 1.161 and 0.431 mg/ml, respectively at 5 mg/ml. The total phenolics content which was found to be higher in methanol crude extract as compared to the dichloromethane crude extract were 107.87g GAE/100g and 58.43g in GAE/100g, respectively. The methanol and dichloromethane extracts of Penicilliopsis sp. were evaluated for their cytotoxic potentials against the human mouth epidermal carcinoma cell line (KB), human epidermal carcinoma of cervix cell line (CaSki), human colorectal cancer cell line (HT29 and HCT119), human breast cancer cell line (MCF7), human ovarian cancer cell line (SCOV3) and the normal human fibroblast cell (MRC5) using the in vitro neutral red cytotoxic assay. Generally, extracts of Penicilliopsis sp. produced ED50 values of more than 20 μg/ml and were therefore considered not cytotoxically active. Extracts were analyzed qualitatively at various concentrations for anti-HPV 16 E6 activities in HPV 16-containing cervical cancer-derived cell line (CaSki) using immunocytochemistry technique. Generally, the HPV 16 E6 oncoprotein was not suppressed in CaSki cells by the crude extracts of Penicilliopsis sp. Therefore, the extracts could be suitable as antioxidative agents and have a potency to become one of antioxidant drugs.